Combinatorial effects of azacitidine and trametinib on NRAS‐mutated melanoma. Issue 4 (6th December 2021) - Hanft, Klara‐Maria; Hamed, Ebrahem; Kaiser, Max; Würtemberger, Julia; Schneider, Michaela; Pietsch, Torsten; Feige, Ursula; Meiss, Frank; Krengel, Sven; Niemeyer, Charlotte; Hettmer, Simone
Abstract: Congenital melanocytic nevus (CMN) syndrome represents a mosaic RASopathy, typically caused by postzygotic NRAS codon 61 mutations, which originate in ectodermal precursor cells and result in melanocyte deposits in the skin and central nervous system (CNS). Affected patients are prone to develop uniformly fatal melanomas in the skin and CNS. Here, we report the case of a 2.7‐year‐old male with CMN syndrome, diffuse leptomeningeal melanosis and CNS melanoma, who underwent experimental therapy with the DNA methyltransferase inhibitor azacitidine in combination with the mitogen‐activated protein kinase (MEK) inhibitor trametinib with exceptional clinical and radiological response. Response to combination therapy appeared to be more durable than the treatment response observed in several other severely affected patients treated with trametinib for late‐stage disease. Correspondingly, concomitant exposure to trametinib and azacitidine prevented development of trametinib resistance in NRAS‐mutated human melanoma cells in vitro. Also, azacitidine was shown to inhibit growth and mitogen‐activated protein kinase 1/2 (ERK1/2) phosphorylation of melanoma cells and act synergistically with trametinib to inhibit the growth of trametinib‐resistant melanoma cells. These observations suggest that azacitidine enhances trametinib monotherapy and may represent a promising candidate drug for combination therapies to enhance the efficacy of MEK inhibitors in RAS‐driven diseases.